Makna “Pemberitahuan Bohong” Pasal 28 Ayat (3) Perubahan Kedua Undang-Undang Informasi dan Transaksi Elektronik (RechtJiva, 2025)
This research is motivated by the issue of the vagueness of the meaning of the phrase “false notification” in Article 28 Paragraph (3) of the Second Amendment to the ITE Law. The choice of the title in this research is that the author considers legal certainty so as not to injure human rights, especially in terms of freedom of speech. The main focus is to find the possible meaning or limitation of what is meant by the phrase “false notification”. This research uses a normative legal research method with a statutory and conceptual approach. The results of the analysis show several possible meanings that can be used as limitations in the phrase “false notification” in Article 28 Paragraph (3) such as Informing the public (through radio, newspapers, etc.) if it is related to the tools or means used and Spreading or Propagating (opinions, ideas, etc.), if the object is in the form of thoughts or other things that aim to influence others. Then the meaning of lie, among others, is like cleaning or making something clean. Nevertheless, in order to uphold legal certainty, it is still necessary to reformulate Article 28 Paragraph (3), so that the possibility of replacement is from the phrase “Notification” to the phrase “Broadcasting or Disseminating”, as well as the replacement of the phrase “lie” to the phrase “Uncertain or Exaggerated or Incomplete”.